2009
DOI: 10.1161/circulationaha.108.820472
|View full text |Cite
|
Sign up to set email alerts
|

Patient Health Status and Costs in Heart Failure

Abstract: Background-Although a variety of prognostic tools have been shown to predict rehospitalization and mortality in heart failure patients, their utility in assessing future costs is less clear. We assessed whether health status assessment with the Kansas City Cardiomyopathy Questionnaire (KCCQ) predicts future costs in stable heart failure outpatients with left ventricular dysfunction after myocardial infarction. Methods and Results-We evaluated 12-month cost utilization data from 1516 heart failure outpatients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 33 publications
2
44
0
2
Order By: Relevance
“…In previous studies, changes of as little as 5 points on the KCCQ summary scale have been shown to correlate with important differences in survival and health- care costs in heart failure patients. 18,19 In our study, the mean between-group differences in the KCCQ summary score 6 and 12 months after enrollment met or exceeded the 20-point threshold considered to signify a very large improvement in heart failure status, and Ͼ75% of surviving patients had at least moderately large (10-point) improvements over baseline. Moreover, the proportion of patients who achieved an excellent outcome at 12 months (defined as surviving with at least a 20-point improvement in the KCCQ summary score) was far greater with TAVR than with standard care (absolute treatment difference, 28%; number needed to treat, 3.5).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In previous studies, changes of as little as 5 points on the KCCQ summary scale have been shown to correlate with important differences in survival and health- care costs in heart failure patients. 18,19 In our study, the mean between-group differences in the KCCQ summary score 6 and 12 months after enrollment met or exceeded the 20-point threshold considered to signify a very large improvement in heart failure status, and Ͼ75% of surviving patients had at least moderately large (10-point) improvements over baseline. Moreover, the proportion of patients who achieved an excellent outcome at 12 months (defined as surviving with at least a 20-point improvement in the KCCQ summary score) was far greater with TAVR than with standard care (absolute treatment difference, 28%; number needed to treat, 3.5).…”
Section: Discussionmentioning
confidence: 56%
“…17 The KCCQ has undergone extensive validation and has been shown to independently predict mortality and healthcare costs in heart failure populations. 18,19 Among outpatients with heart failure, small, moderate, or large clinical improvements as rated by treating physicians corresponded with changes in the KCCQ summary score of Ϸ5, 10, and 20 points, respectively. 17 Generic health status was evaluated with the Medical Outcomes Study Short-Form 12 (SF-12) Health Survey.…”
Section: Measurement Of Health Statusmentioning
confidence: 99%
“…22,39 NYHA class is notoriously difficult to standardize and furthermore has been shown to be a poor predictor of future cost in patients with LV dysfunction and recent myocardial infarction. 25 However, 6-minute walk times and quality of life indicators are consistent with mild HF. The Kansas City Cardiomyopathy Questionnaire has been shown by Chan et al 25 to more accurately identify HF patients likely to be high utilizers of health resources in the future.…”
Section: The Vital Question Of Costmentioning
confidence: 99%
“…25 However, 6-minute walk times and quality of life indicators are consistent with mild HF. The Kansas City Cardiomyopathy Questionnaire has been shown by Chan et al 25 to more accurately identify HF patients likely to be high utilizers of health resources in the future. Utilizing more sophisticated yet accessible tools such as the Kansas City Cardiomyopathy Questionnaire instead of NYHA class might prove to hold great utility, potentially streamlining the delivery of a limited resource to patients with the most to gain, patients who, by extension, are the ones who would make CRT as economically advantageous as possible.…”
Section: The Vital Question Of Costmentioning
confidence: 99%
See 1 more Smart Citation